Desorption of CO from individual ruthenium porphyrin molecules on a copper surface via an inelastic tunnelling process. Issue 45 (23rd May 2017) - Omiya, Takuma; Poli, Paolo; Arnolds, Heike; Raval, Rasmita; Persson, Mats; Kim, Yousoo
Abstract : The coordination of CO to metalloporphyrins changes their electronic and magnetic properties. Abstract : The coordination of CO to metalloporphyrins changes their electronic and magnetic properties. Here we locally desorb CO molecules from a single ruthenium tetraphenylporphyrin carbonyl (CO–RuTPP) on Cu(110) using STM. The desorption is triggered by the injection of holes into the occupied states of the adsorbate using an unusual two-carrier process.